GREENHOUSE WHITEFLY - BABAYAN, ARMAN HRANTOVICH (International Journal of Psychosocial Rehabilitation, 2020)
- In this article we will consider such a well-known pest as the greenhouse whitefly. The danger to plants from this pest is due not only to the fact that the insect damages the leaves. Whitefly can be a carrier of many pathogenic phytoviruses. That is why it is necessary to deal with the pest at the first sign of plant damage, as well as timely preventive measures to protect plants.